Fabrication of ZnFe2O4@g-C3N4 for enhanced photo-fenton effect and visible light-driven organic dye degradation - Leyan Li; Wang Jianhua; Huihui Fang (Scientific Reports)
Abstract This study successfully synthesized a magnetically recoverable ZnFe₂O₄@g-C₃N₄ heterojunction photocatalyst by anchoring ZnFe₂O₄ nanoparticles (20–30 nm) onto a mesoporous g-C₃N₄ framework via a hydrothermal method. Comprehensive characterizations, including XRD, SEM, TEM, and UV–Vis spectroscopy, confirmed the formation of a porous multilayer structure with uniform dispersion of ZnFe₂O₄ nanoparticles on the g-C₃N₄ surface. Tight interfacial heterojunction bonding significantly enhanced photogenerated charge separation. BET analysis revealed a high specific surface area ( 855.9 m2/g) due to the mesoporous architecture, while TEM further elucidated efficient electron transport at the heterojunction interface. Under visible light irradiation, the composite achieved complete degradation of methylene blue (MB) through synergistic effects of extended light absorption, accelerated interfacial charge transfer, and high-density active sites. At an optimal ZnFe₂O₄ loading of 59.1 wt%, the degradation efficiency reached 99.99% within 40 min, with a rate constant (0.253 min⁻1) ninefold higher than that of pristine g-C₃N₄. The introduction of H₂O₂ activated a photo-Fenton mechanism, further boosting hydroxyl radical (·OH) generation and improving degradation efficiency by 12 times. Additionally, the inherent ferromagnetism of ZnFe₂O₄ enabled facile magnetic recovery, with catalytic activity retention exceeding 95% after 10 consecutive cycles. The ZnFe₂O₄@g-C₃N₄ heterojunction photocatalyst developed in this work integrates high degradation efficiency, magnetic recyclability, and structural stability, demonstrating significant potential for industrial wastewater treatment and environmental remediation. This study provided a novel strategy for designing sustainable photocatalytic systems, offering insights into dual-mechanism (photocatalytic/Fenton-like) synergies and scalable heterojunction engineering for advanced pollutant degradation.